A showdown between bilingual and mainstream education: the impact of language of instruction on learning subject content knowledge - Oattes, Huub; Fukkink, Ruben; Oostdam, Ron; de Graaff, Rick; Wilschut, Arie (International journal of bilingual education and bilingualism, 2022)
Bilingual education has become popular in many countries in the last two decades. It is generally acknowledged that learning a second language (L2) through subject content has a positive impact on students' L2 learning, but there is less agreement on whether this also applies to learning subject content knowledge in and through L2. This cross-sectional study compared Dutch pre-university mainstream and bilingual education students in grades 7 and 9 on a history knowledge test, taking into consideration the language of instruction and testing. Students were also tested on their motivation to learn and affinity with history, because of the alleged higher motivation bilingual education students bring to the classroom. Multilevel analyses showed that bilingual education students in grade 7 lagged behind in the English part of the test but performed at the same level in the Dutch part. 9th bilingual education graders on the other hand performed significantly better on the knowledge test than 9th mainstream graders in both L2 and L1, thus providing evidence for the non-detrimental effect of bilingual education on the acquisition of subject content knowledge.